RETAIL STORE EFFECTIVENESS IN AFFECTING PURCHASE DECISIONS - Aziz, Abdul (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The increasingly fierce business competition in the era of globalization makes every company must be able to compete and determine the right strategy. This study aims to determine the effect of store atmosphere and product completeness on purchasing decisions at the Agus Jaya store. The method used is quantitative analysis with multiple regression analysis techniques and for the sample obtained as many as 30 respondents with purposive random sampling technique. From the partial and simultaneous test results show that the store atmosphere and product completeness variables have a positive and significant effect on consumer purchasing decisions. So that the analysis of the test results of the Agus Jaya store must establish an atmosphere as attractive and comfortable as possible for visiting customers to create a happy impression for visiting customers besides that the completeness of product variants is needed so that consumers can freely choose according to the needs they want.